Knowledge Sharing Practices In Malaysian MSC Status Companies - Wei, Chong Chin; Teh, Pei-Lee; Asmawi, Arnifa (Journal of Knowledge Management Practice, 2012)
This paper aims to investigate the effect of organizational influences (i.e., organizational culture, coworkers’ support, rewards and organizational structure) on organizational practices that stimulate knowledge sharing. This study adopts a quantitative approach. Questionnaires were administered to 250 companies listed in the MSC status Malaysia Company Directory. The data analysis was based on 199 usable responses. Multiple regression analysis was performed to test the hypotheses. Innovation, coworkers support and intrinsic rewards are positively related to knowledge sharing practices. In addition, organizational structure that facilitates the development of new ideas and allows free flow of information is found to be important in promoting knowledge sharing. Extrinsic reward is also found to have an inverse relationship with knowledge sharing. This study provides an empirical evidence for a new model that shows the culture of innovation, management support, organizational structure and reward systems are implicated in individuals’ knowledge sharing behaviour.